1983
DOI: 10.1055/s-2007-969851
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Separation and Quantitative Determination of Biflavones in Leaves fromGinkgo biloba

Abstract: An HPLC method for separation and quantitative determination of biflavones in crude leaf extracts from GINKGO BILOBA L. is described. A system using a Lichrosorb(R)-Diol column and the ternary elution system: hexane-chloroform-tetrahydrofuran, was suitable for separation of sciadopitysin, ginkgetin, isoginkgetin and bilobetin. The biflavones were detected at 330 nm; their calibration curves were established and their response factors were calculated using acacetin as internal standard. This method was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…All the HPLC traces show five distinct groups of substances: 1) the very polar ones, like phenolic and kynurenic acids (compounds 1-2), 2) the flavonol glycosides (3-8), 3) the acylfiavonol glycosides (9-10), 4) the flavone dimers (11-14), 5) two unidentified peaks (15)(16). amount is near than that of the acylfiavonol glycosides.…”
Section: Analysis Of the Ginkgo Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the HPLC traces show five distinct groups of substances: 1) the very polar ones, like phenolic and kynurenic acids (compounds 1-2), 2) the flavonol glycosides (3-8), 3) the acylfiavonol glycosides (9-10), 4) the flavone dimers (11-14), 5) two unidentified peaks (15)(16). amount is near than that of the acylfiavonol glycosides.…”
Section: Analysis Of the Ginkgo Extractsmentioning
confidence: 99%
“…This ancient tree also synthesises dimeric flavonoids derived from amentoflavone (5) the pharmacological properties of which are very interesting (6)(7)(8)(9)(10)(11)(12)(13)(14). In previous papers we studied their separation by HPLC (15) and showed that their seasonal variations presented higher amounts at the end of the vegetative cycle (16).…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin was also prepared by hydrolysis of luteolin-7-glycoside, which was extracted from the leaves of Hieracium pilosella L. (45). Sciadopitysin, ginkgetin and bilobetin were purified from a crude mixture extracted from green Ginkgo biloba L. leaves, according to the techniques already developed (46,47). Amentoflavone was prepared from leaves of Viburnum lantana L., using a reported procedure (48).…”
Section: Experimental Chemicalsmentioning
confidence: 99%
“…Bilobetin (Figure 1) is a biflovone isolated from the leaves of Ginkgo biloba (Briançon-Scheid, Lobstein-Guth, & Anton, 1983). The compound exerts a variety of pharmacological activities: (a) it inhibits the production of the inflammatory cytokines, cyclooxygenase and nitric oxide in macrophases (Baek et al, 1999), cAMP-phosphodiesterase in adipose tissue (Saponara & Bosisio, 1998) and human thrombin (Chen et al, 2019); (b) it suppresses lymphocyte proliferation (Lee et al, 1995); (c) it ameliorates hyperlipidemia, lipotoxicity and insulin resistance (Kou et al, 2012); and (d) it stimulates osteoblast differentiation (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%